Tingkat Efektivitas Religious Coping Sebagai Penanganan Stres pada Individu Muslim: Systematic Literature Review - Salma Yulia Widayanti; Intan Islamia; Annisa Fitriani (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Stress has developed into an increasingly common mental health issue worldwide. This study aims to use a systematic literature review (SLR) to identify the effectiveness level of various types of religious coping efforts using PRISMA 2020 by screening 20 scientific articles based on inclusion and exclusion criteria. Based on the data obtained, the most commonly used religious coping method by individuals is prayer at 25.71%, indicating the significant role of spirituality in facing challenges. Next, faith encompasses the relationship with God at 14.29%. Additionally, involvement in social support and reading the Quran reaches 11.43%, highlighting the importance of social networks. The practice of dhikr and patience each contributes 8.57% and 5.71% respectively. Fasting, prayer, gratitude, repentance, and visiting holy places also indicate the use of various approaches in coping with stress, which is relatively low at 2.86%. Factors influencing religious coping as a stress management strategy include gender, income, education, marital status, and environment. Overall, these findings indicate that spirituality and religiosity play an important role in individual coping mechanisms.